On Sexuality / Three Essays on the Theory of Sexuality and Other Works - Freud Sigmund (Penguin Books, 1991)
This volume contains all of Freud's major writings on sexuality. On Sexuality, Three Essays on the Theory of Sexuality, The Sexual Aberrations, Infantile Sexuality, The Transformations of Puberty, The Sexual Enlightenment of Children, On the Sexual Theories of Children, Family Romances, A Special Type of Choice of Object Made by Men, On the Universal Tendency to Debasement in the Sphere of Love, The Taboo of Virginity, Two Lies Told by Children, On Transformations of Instinct as Exemplified in Anal Erotism, The Infantile Genital Organization, The Dissolution of the Oedipus Complex, Some Psychical Consequences of the Anatomical Distinction Between the Sexes, Fetishism, Libidinal Types, Female Sexuality.